Changes in Pharmacists' Perceptions After a Training in Opioid Misuse and Accidental Overdose Prevention. Issue 1 (2019) - Eukel, Heidi N.; Skoy, Elizabeth; Werremeyer, Amy; Burck, Siri; Strand, Mark
Abstract : Introduction: Continuing education is needed for health professionals to take an active role in reversing the opioid crisis. This report describes the results of training to promote behavioral change by altering pharmacists' perceptions toward opioid misuse through the provision of content-related education. Methods: A free 3-hour opioid misuse and overdose prevention training program was developed and delivered to 43 community pharmacists. The training consisted of five modules addressing the disease of addiction, risks associated with opioids and accidental overdose, the role of naloxone, opioid dispensing and consultation pearls, and effective ways to communicate with patients about opioids. A paired analysis was performed from a 12-item survey delivered before and after the training program to assess changes in pharmacists' perception. Results: Five items showed a statistically significant ( P < .05) change in perceptions after the training. Significant changes were reported for opioid addiction being outside the control of the affected person, the role of family history in prescription drug abuse, the value of counseling to support patients at risk of prescription opioid abuse, the value of screening tools, and the importance of viewing things from the patient's perspective. Correlation analysis identified that pharmacists' views on their role in the fight against the opioid epidemic and their agreement in the value to screen for opioid misuse were most closely related to the desire for behavioral change. Discussion: A training program influenced pharmacists' attitudes and perceptions about targeted behaviors and associated with the value of screening for opioid misuse or overdose risk and counseling patients about the benefits and risks of opioids.